Investigating the effect of molasses concentrations on the characterization of evaporation boat waste for crucible materials candidate - Widodo, Rahmat Doni; Rusiyanto, R.; Athoillah, A.; Setiadi, Rizki; Bahatmaka, Aldias; Darsono, Febri Budi; Fitriyana, Deni Fajar; Siregar, Januar Parlaungan; Cionita, Tezara; Ismail, Rifky; Bayuseno, Athanasius P.; Irawan, Agustinus Purna; et al. (Asian Research Publishing Network, 2023)
The crucible is a container wherein metallic materials are melted in order to generate new objects or alloys. Crucibles are typically formed of ceramic, graphite, silicon-carbide, and steel. Until now, there has been no study on the use of evaporation boat waste and molasses for the manufacture of crucibles. This study shows that molasses was used for binding the crucibles production formed from evaporation boats waste. The goal of this research was to ascertain how using molasses affected the properties of the crucible produced. Evaporation boat waste is made into powder (mesh 80) using a hammer mill. Molasses, evaporation boat waste powder and water with a certain concentration are mixed homogeneously using a mixer. The mixed material is put into a mold that has been adjusted to ASTM C1161-18, and then the compaction process is performed (20 MPa) to produce a green body. The resulting green body underwent a 16-hour drying time in an oven set at 100°C. Afterward, it was sintered for 240 minutes at 1150°C. The specimens in this study were characterized using XRD, SEM, density, hardness and 3-point bending tests. The test results show that molasses as a binder in the manufacture of crucible specimens does not result in the formation of a new crystalline phase. 5% molasses produced the best specimens. In specimens with 5% molasses, the density, hardness, flexural strength, and weight percentage (%) crystal phase of BN and TiB2 were 2.25 g/cm3, 61.6 HRA, 49.96 MPa, 67.5%, and 32.5%.